Making policing obsolete: the harms of policing and an abolitionist social work response - Toraif, Noor (Social work, white supremacy, and racial justice, 2023)
This chapter identifies the harms of relying on policing as a response to social problems, conceptualizes abolitionism as a political movement, and argues that a distinctly abolitionist form of social work can and should help displace policing. The chapter further argues that this abolitionist social work has six defining tenets and demonstrates how these tenets reflect the components of abolitionist politics and are reflected in successful nonpolicing methods of responding to several social problems, including homelessness, substance use and addiction, and mental health crises. The chapter argues that abolitionist social work can contribute substantially to policing’s displacement and the prefiguration of a world in which police and policing are obsolete. This is especially urgent, given the expansion of policing to many social domains in the United States over the last half century, and the disproportionate harms policing has imposed on Black, Indigenous, and communities of color and the poor.